Adenocarcinoma in a Tailgut Cyst: A Rare Case Report - Songül ŞAHIN; Nuray KEPIL; Şebnem BATUR; Sibel ERDAMAR ÇETIN (Federation of Turkish Pathology Societies, 2020)
Developmental cysts are the most common retrorectal area cysts observed in adults. Tailgut cysts tend to be multicystic, and their lining epithelium may display the characteristics of columnar, musin-secreting columnar, ciliated, transitional or squamous epithelia. While the large majority of cysts tend to be benign, several malignant cases have been reported, with adenocarcinoma and carcinoid tumors constituting the more common types of malignant tailgut cysts. A 55-year-old female patient presented to our hospital with complaints of swelling in the gluteal region. Following morphological, histomorphological and immunohistochemical evaluations, a diagnosis of a moderately differentiated adenocarcinoma arising from a tailgut cyst was made. Tailgut cysts are infrequent diseases but adenocarcinoma arising from a tailgut cyst is extremely rare. In rare cases, developmental cysts may undergo malignant transformation that warrants an accurate morphological and histomorphological assessment, as well as numerous samplings, for an accurate diagnosis.